Understanding and Managing Threats to the Environment in South Eastern Europe - Meško, Gorazd; Dimitrijević, Dejana; Fields, Charles B. (NATO Science for Peace and Security Series C: Environmental Security,, 2011)
This volume presents reflections on a variety of environmental issues in South-Eastern Europe from diverse contemporary scientific disciplines. The contributions address many crucial issues including national environmental policies, economic instruments for preventing crimes against the environment, international waste trafficking, threats to air, water and soil due to mining, management of dump areas, environment protection and food safety from a perspective of public health. The book will be a useful resource for researchers, developers and decision makers interested in the stability and sustainable development of the South-Eastern European countries.